RISK FACTORS ASSOCIATED WITH MEDICAL DEVICE–RELATED PRESSURE INJURIES AMONG PATIENTS IN INTENSIVE CARE UNIT, NISHTAR HOSPITAL, MULTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Medical device–related pressure injuries (MDRPIs) represent a critical yet often underrecognized source of patient morbidity in intensive care settings. Critically ill patients are frequently exposed to multiple invasive and non-invasive medical devices, increasing their vulnerability to pressure-induced skin damage.Objective: This study aimed to identify the risk factors associated with the development of MDRPIs among adult patients admitted to the Intensive Care Unit (ICU) at Nishtar Hospital, Multan.Methods: A case-control observational study was conducted over six months, involving 44 ICU patients, including 22 cases with MDRPI and 22 controls without MDRPI. Data were collected using a structured checklist assessing demographic information, clinical parameters, device type, Braden scale scores, and physiological characteristics. Logistic regression analysis was performed to determine significant predictors of MDRPIs.Results: MDRPIs most frequently occurred in the oral cavity (36.36%), followed by the neck, arms, hands, and femoral region. Stage II pressure injuries were predominant (59.09%). Significant predictors included sedation administration (p < 0.05), mechanical ventilation (p < 0.05), edema (p = 0.05), GCS score (p < 0.05), Braden risk score (p = 0.05), and prolonged ICU stay (p = 0.05). Patients with extended hospitalization and multiple medical devices were at higher risk of developing MDRPIs.Conclusion: MDRPIs are influenced by both device-related and patient-specific risk factors. Early risk screening using standardized assessment tools, vigilant skin monitoring, minimizing device pressure, and timely repositioning are essential to reduce MDRPI incidence. The study underscores the need for structured prevention protocols and continuous staff education to enhance ICU patient safety.